PERATURAN PERUNDANG-UNDANGAN DAN KONTRAK PEMBIAYAAN KONSUMEN DALAM PERSPEKTIF KEADILAN - Prasetyowati, Endang (DiH: Jurnal Ilmu Hukum, 2017)
The implementation of consumer finance vulnerable to the emergence ofÂ  injustice. Injustice appear because they had not been accommodation of different interest in consumer finance by a law especially in this matter is in form of act. Problematic in this research whether justice in the regulation and contract consumer finance been fulfilled? The research results show that justice for those consumers in legislation regulation for consumer finance have been fulfilled. The theory distributive justice, should everyone gets what is rights or his ninth but in consumer finance, consumer rights is ignored. Who are attention here is consumer finance institution as creditors and status as the economic strong.